UJI BANDING METODA PELINDIAN LOGAM KROM CARAROTARY AGITATOR DENGAN ULTRASONIC CLEANER MENGGUNAKAN BAHAN ACUAN TANAH BERSERTIFlKAT - Ardeniswan Ardeniswan (Jurnal Kimia Terapan Indonesia, 2011)
A comparative test of leaching procedure of the metal chromium (Cr) were conducted between Rotary Agitator and Ultrasonic Cleaner by using certified soil reference materials (CRM) lot number 118 097 APG having a true value of total chromium concentration of 16.7 ± 0.333 mg/L which is used as an material comparison. The result shown that a average concentration result of chromium leached test using Rotary Agitator is 14,18 ± 0,3407 mg/L, and gave recovery 94,92 %. A while the average concentration result of chromium leached test using Ultrasonic Cleaner is 13,64 ± 0,118 mg/L,and gave recovery 91,68 %. Comparison study between Rotary Agitator and Ultrasonic Cleaner equipments didn't shows any significant difference,where tcomputed< ttabularwhich indicates the null hypothesis (HJ is accepted with value a 95 %.Keyword: Certified Reference Material, leached test, Rotary Agitator, ultrasonic Cleaner